AL-HAMZAH WA ASWĀT AL-‘ILLAH BAYN AL-WAṢF AL-NUṬQIY WA AL-BUNYAH AL-MUQAṬṬA’AH - Mustafa Bani Dhiyab; Muhammad Majid al-Dakhil; Majdi Husayn Ahmad Syahadat (Universitas Islam Negeri Ar-Raniry, 2016)
This study investigates the vowels and hamza as it offers the phoenetics’ characteristics for both vowels and hamza in their separate contexts and for the effect of phoenetics contexts on their phoenetics’ characteristics. This study concludes that there is a symmetrical relationship between the characteristics of the vowels and hamza especially when the vowel comes after alif at the end of the word. In addition to waht have been mentioned, this study gropes the effect of syllabic structure in Arabic on the phoenetics’ sequences for the vowels which lead to the convert of waw and ya to hamza after alif. This conversion is discussed despite the difficulties of the articulations of the sounds. Was the hamza suitable phoenetics’ choice for this case? These things are discussed in the following article.